Microcredit and gender empowerment: policy implications for sustainable agricultural development in Eritrea. Issue 1 (2nd January 2017) - Bahta, Yonas T.; Strydom, Dirk B.; Donkor, Emmanuel
ABSTRACT: Sustainable agricultural development requires capital investment. However, farmers in Africa are constrained by inadequate access to microcredit. Therefore, this article examines the extent to which gender influences access to microcredit. The empirical results showed that women are less likely to be able to access microcredit, compared to men. The study also found that separate sets of factors including assets endowment, socio-economic, institutional, and technological factors significantly affected women's and men's access to microcredit. The article suggests that to promote sustainable agricultural development, gender differential should be critically considered in designing microcredit schemes that target farmers in Africa.